Acute kidney injury as the presenting complaint of ceftazidime-induced immune-mediated haemolysis. Issue 11 (14th November 2019) - Ferro, Ashley; Griffiths, Meryl; Smith, Rona; Fry, Andrew
Abstract : We present the case of ceftazidime-induced immune-mediated haemolysis with associated acute kidney injury in a 43-year-old woman. The patient initially presented to the regional cystic fibrosis centre for treatment of an infective exacerbation of cystic fibrosis. After initiation of ceftazidime (a third-generation cephalosporin), renal function rapidly deteriorated and a fall in haemoglobin was noted. On transfer to our care, a haemolysis screen identified immune-mediated haemolysis, and renal biopsy confirmed the finding of acute tubular necrosis secondary to haem pigment. The patient's renal function deteriorated such that she required haemodialysis, although she subsequently recovered and is now dialysis-independent. Although acute haemolytic reactions are recognised with third-generation cephalosporins, this is the first reported case of ceftazidime-induced immune-mediated haemolysis with acute kidney injury. Given the increased frequency of cephalosporin usage, it is important for both nephrologists and general physicians to be aware of this rare but very serious complication.